Mapping release and propagation areas of permafrost-related rock slope failures in the French Alps: A new methodological approach at regional scale - Cathala, Maëva; Magnin, Florence; Ravanel, Ludovic; Dorren, Luuk; Berger, Frederic; Bourrier, Franck; Zuanon, Nicolas; Deline, Philip (CCSD, 2024)
International audience Permafrost-affected rockwalls are increasingly impacted by the effects of climate change and rising air temperature leading to rock slope failures, threatening human lives and infrastructure. Populations and policy makers need new methods to anticipate these potential hazards and their consequences. The aim of this study was to propose a mapping approach of susceptible release areas of rock slope failures and resulting runout distances at a regional scale to identify hotspots for hazard assessment. To do so, we used an inventory of 1389 rock slope failures (volume > 102 m3) recorded in the Mont-Blanc massif from 2007 to 2019 and determined the topographical and permafrost conditions that are most prone to their triggering using a digital terrain model and a permafrost map. These conditions are used in a multi-criteria GIS approach to identify potential unstable slopes at the French Alps scale. Then, the potential release area map is used as input to map the runout of potential events, using a propagation model based on a normalised area dependant energy line principle. The resulting maps of release and propagation areas could be used to point out human assets and lakes which could be impacted by rock slope failure hazards. In this communication we will show how theses maps can be used to identify potential hotspots for a regional hazard assessment. This work is a first step to identify hot spots for a regional hazard assessment where more detailed analyses will be required to evaluate potential risks at a local scale.